To the Last Man : A Novel of the First World War - Shaara, Jeff (London Bantam Books, 2006)
Spring 1916, and three great armies - French, British and, on the other side of the wire, German - are locked in a stalemate of mud and blood on Europe's Western Front. On the ground, young British soldiers lose their innocence in the hell that is No Man's Land, while in the skies above the trenches a new breed of warrior comes of age.
Keywords: Americans -- British